Human Capital, Occupational Status, and Social Integration of Pakistani Immigrants in Germany: Gender Perspectives - Sadaf Mahmood (Kassel University Press GmbH_Legacy, 2016)
In the early 21st century human capital is an essential ingredient for economic development at the national as well as individual level. Yet, considerable international and gender specific differences are prevailing which are relevant in the context of international labor mobility and in the global race for talents. The present research focuses on human capital formation and transfer of Pakistani migrants in Germany, its impact on their professional standing, and their social integration. The results are providing important input for shaping policy measures in Germany and Pakistan. Sadaf Mahmood was born in Faisalabad, Pakistan, in 1988. She completed her M.Sc. in Rural Sociology from the University of Agriculture, Faisalabad in 2010. She started her professional career as a lecturer at the Government College University, Faisalabad (GCUF) in 2011 from where she is currently on study leave. She was granted an overseas PhD scholarship by the GCUF. In 2012, she started her PhD studies at the Department of Development Economics, Migration and Agricultural Policy at the University of Kassel, Germany, where she obtained her degree in 2016. Her research has been published in several Journals. Her research interests include social integration, human capital, gender and international migration and development.